ChemInform Abstract: Recent Advances in C—H Bond Aminations Catalyzed by Ruthenium Porphyrin Complexes. Issue 35 (August 2016) - Intrieri, Daniela; Carminati, Daniela Maria; Gallo, Emma
Abstract: Review: 71 refs.